2004
DOI: 10.1242/jeb.00907
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of sodium chloride uptake in hyperregulating aquatic animals

Abstract: SUMMARYThe emphasis in this review will be on Na+ absorption across the skin and gills of vertebrates and the gills of crustaceans. However, some recent studies of Cl– uptake, especially in crustaceans, will also be described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
131
0
23

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(162 citation statements)
references
References 127 publications
(103 reference statements)
8
131
0
23
Order By: Relevance
“…More specifically, the gill Na + , K + ATPase, located mainly in chloride cells, requires energy input and plays an important role in osmoregulation in both hyperosmotic (Jobling, 1995;Evans et al, 2005) and hyposmotic (Evans, 2008;Parks et al, 2008) environments. The activity of this ATPase spends at least half of the energy consumed during Na + /H + exchange in ionocytes (Kirschner, 2004). For this reason, Na + , K + ATPase is considered to be a good biomarker of osmoregulation in teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the gill Na + , K + ATPase, located mainly in chloride cells, requires energy input and plays an important role in osmoregulation in both hyperosmotic (Jobling, 1995;Evans et al, 2005) and hyposmotic (Evans, 2008;Parks et al, 2008) environments. The activity of this ATPase spends at least half of the energy consumed during Na + /H + exchange in ionocytes (Kirschner, 2004). For this reason, Na + , K + ATPase is considered to be a good biomarker of osmoregulation in teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether any of these systems was utilized to maintain Na + homeostasis or for recovery, we assessed the possible use of these pathways under basal and recovery conditions. Previous studies have determined that Na + uptake can occur in the absence of ambient Cl -availability (Krogh, 1938;Krogh, 1939;Kirschner, 2004), although the rate may be reduced relative to conditions that provide Cl - (de With et al, 1987). Considering this evidence that Na + uptake can occur in Cl --free conditions, we were not surprised to find a lack of dependency on Cl -.…”
Section: Discussionmentioning
confidence: 50%
“…One possible characteristic of pathways involved in Na + recovery could be dependency on availability of extracellular anions (de With, 1980;de With et al, 1987). Uptake of Na + in many freshwater organisms requires Cl - (Kirschner, 2004) and the possibility of HCO 3 --dependent Na + uptake via a Na + /HCO 3 --dependent carrier system exists (Perry et al, 2003). The observed stimulated Na + uptake associated with recovery from ECF release was attributed to both increased transport capacity and affinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study we found that, besides ouabain (normoxic condition), hypoxia reduced 86 Rb + effluxes from the basolateral to the apical side of the gill hemilamella, where 86 Rb (K + ) ions enter the cells by the activity of Na + , K + -ATPase, at the basolateral side. In the hyperosmoregulating Carcinus the Na + /K + -pump actively transports K + into the cytoplasm of the gill epithelial cells from which it passively diffuses out of the cell through K + channels at both sides of the epithelium (Kirschner, 2004).…”
mentioning
confidence: 99%